(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Perfluoroalkyl substances are emerging environmental pollutants of increasing concern that are used extensively in industry. They are highly recalcitrant and pose environmental and public health hazards. This study is among the few assessing the degradation of perfluorohexane sulphonate (PFHxS) in laboratory-based studies using indigenous hydrocarbon-degrading fungi and bacteria from Nigerian soils. The isolates were enumerated and characterised via standard microbiological techniques. The bacteria were further identified using an Analytical Profile Index®20E kit. The utilisation capacity and tolerance indices of the isolates were determined via media dilution. A total of 4 fungal and 8 bacterial isolates were identified for study. Pseudomonas putida (27.5%) and Klebsiella (15.0%) dominated amongst the bacteria, while Alternaria (28.0%) and Aspergillus niger (36.0%) dominated amongst the fungi. The greatest mean abundance after exposure to PFHxS was seen with Trichoderma sp. (300–500 SFU/mL) and Alternaria sp. (900–1000 SFU/mL). Amongst the bacteria, the highest mean counts were found for Bacillus cereus (109–670 CFU/mL), Pseudomonas putida (267–720 CFU/mL), and Serratia marcescens (312–610 CFU/mL). There were statistically significant differences (p≤0.05) in the abundance of the bacteria and fungi both between groups and within groups. From the tolerance indices, the bacteria tolerated PFHxS better than the fungi. Only Alternaria was able to degrade PFHxS amongst the fungi, while all the bacterial isolates showed PFHxS degradation capacity except Escherichia coli and Flavobacterium. From the results, it can be concluded that organisms like Alternaria, Bacillus cereus, Pseudomonas putida, and Serratia marcescens would be useful bioresources in the environmental decontamination of PFHxS.